Camtasia as English Learning Video in EFL Classroom: Response of its Implementation - Subakti, I Made Puja; DAE, Agustini (Universitas Pendidikan Ganesha, 2020)
Since Educational industry 4.0 reflects the current style of teaching and learning process, the integration of technology-based learning media has been highly demanded. Thus, various types of learning media including video have been widely implemented. This policy was then the basis of this present study to describe teachers’ and students’ response towards the implementation of animated learning video developed by using Camtasia in elementary schools. This study made use of a descriptive qualitative study. The data were collected through observation, questionnaire, and interviews. The result of this study clearly indicates that by offering animated learning video, the learning activity becomes more attractive even more affects the students’ understanding, especially in building vocabulary mastery. As the result, the animated learning video developed has been acknowledged as an effective learning media. As the advantage, this study can enrich students’ learning experience in learning English.